Knowledge, Behavior, and Attitude towards HIV/AIDS among Street Vendors in Nepalgunj, Banke - Basnet Pokhrel, Sabitra (Academia Research Journal, 2023)
This research article aims to investigate the existing knowledge, behavior, and attitude towards HIV/AIDS among street vendors in Nepalgunj, Banke. Street vendors are an informal sector of the economy, and their vulnerability to HIV/AIDS is a growing concern. The study seeks to fill the gap in research on this specific group and shed light on their understanding of HIV/AIDS, prevention methods, and socio-economic background. The research methodology includes a combination of primary and secondary data collection methods. Data was collected through ethnographic methods, including case studies, individual surveys, participant observation, and focus group discussions. A total of 50 street vendors were randomly selected for the survey, along with case study participants and focus group discussion informants. The collected data was analyzed using thematic analysis to identify patterns and trends. The findings indicate that street vendors in Nepalgunj, Banke, are predominantly from India and have a wide age range, with the majority falling between 31-35 years old. The study reveals that most street vendors have heard about HIV/AIDS through various media sources, primarily radio programs. However, their knowledge about HIV/AIDS is limited, with some misconceptions and biases prevailing. Condom use among street vendors is low, contributing to their vulnerability to HIV transmission. The research also highlights the challenges faced by street vendors, such as lack of social security, poor living conditions, and occupational hazards. Despite being well-informed about HIV/AIDS, translating knowledge into behavioral practices remains a significant challenge for street vendors. The study concludes that interventions are needed to improve the knowledge, behavior, and attitudes of street vendors towards HIV/AIDS. These interventions should focus on raising awareness, promoting condom use, and addressing socio-economic vulnerabilities. Additionally, efforts should be made to integrate street vendors into social security programs and provide better working and living conditions. Overall, this research contributes to the sociological understanding of HIV/AIDS among street vendors in developing countries like Nepal and emphasizes the importance of tailored interventions for this vulnerable population.